ACUTE EFFECTS OF ELASTIC AND RIGID TAPING AT THE ANKLE ON AGILITY AND SELF–CONFIDENCE OF FUTSAL PLAYERS - SANTINIYOM, Nonthalee; INTAPANYA, Theerawith (Journal of Sports Science and Technology, 2021)
Futsal is a sport requiring speed and ongoing movement, possibly resulting in ankle pain or injuries. For this reason, futsal players rely on taping to alleviate and prevent injuries prior to competition, affecting their agility and self-confidence. The objective of this research was to investigate and compare acute effects of elastic and rigid taping on at the ankle that on agility and self-confidence of futsal players. This study used cross-over design. The sample of 24 male futsal players in Thailand National Sports University team, Sukhothai Campus with an average age of 19.25±1.51 years used three types of taping, namely: elastic-taping, rigid-taping, and non-taping. Taping duration distance was 72 hours for individual type of taping. Agility was assessed with the FAF's Slalom test and self-confidence was assessed with the CSAI–2R. Results were analyzed and data were compared with One-way repeated measures ANOVA. The results revealed that there were no statistically significant differences between elastic-taping and non-taping group in agility at the 0.05 level. The elastic taping group and the non-taping group had better agility than the rigid taping group with a statistical significance level of 0.05. In addition, the elastic-taping group and rigid taping group had a high level of self-confidence with a statistically significant indifference at the 0.05 level. The non-taping group had a moderate level of self-confidence. The elastic-taping group and rigid group had higher self-confidence than non-taping group with a statistical significance level of 0.05. Therefore, the findings could be concluded that elastic taping at the ankle had higher effects on agility than rigid taping. Elastic and rigid taping at ankle could enhance self-confidence of players than non-taping case. (Journal of Sports Science and Technology 2021; 21 (2):74-85) (Received: 18 February 2021 , Revised: 8 July 2021, Accepted: 9 July 2021) Keywords: Elastic Taping/ Rigid Taping/ Self–Confidence/ Agility/ Futsal Players *Corresponding Author: Nonthalee SANTINIYOM Faculty of Sports and Health Science, Thailand National Sports University Sukhothai Campus, Sukhothai, THAILAND 64000 Email: i.nonthalee@gmail.com